Success Factors in Achieving Socio-Economic Development in Local Communities - Haudi, .; Aseh, Khairi; Kenny, Kamal; Pathmathan, P. Ravindran (Archives of Business Research, 2020)
Previous studies have shown that socio-economic growth of rural areas can be affecting by a complex of factors. Poverty, for instance, is not a single factor but rather is characterized by several physical and psychosocial stressors. The partnership between private and public sectors in Malaysia has demonstrated empirical success as reinforced by the needs to address the gaps and demands of the local community. However, there are many rural areas that are rich with natural resources are not fully explore and develop. Rural areas indeed have significant natural, human, economic and cultural potential to support their developments. Over the years, the importance of economic diversification and rural development has been increasing significantly and has eventually opens up new opportunity to discuss on how to using resources at the full value and in a sustainable way. These initiatives would later provide crucial information that will complement relevant literatures for the stakeholders to plan for a better socio-economic development in Malaysia, in particular for this study, Raub. Therefore, this study examines the socio-economic demands and challenges of the local population in Raub, Pahang to recommend relevant assistance and interventions required. The overall results of this study reveal the gaps faced by the community in the District of Raub in the context of social and economy. This study was carried out via a structured survey throughout the district involving 300 respondents and also complemented with a face-to-face interview carried out with key stakeholders.